THE EFFECT OF SERVICE QUALITY AND FACILITY ON CUSTOMER LOYALTY WITH CUSTOMER SATISFACTION OF KRL (COMMUTER LINE) JABODETABEK AS A MODERATOR - Faris Naufal Ramadhan; Imam Suryono; Diansyah (RADJA PUBLIKA, 2025)
This research ensures the influence of service quality and facility on customer loyalty. Then look again at the customer satisfaction relationship in strengthening the service quality and facility variables. Current research provides a comprehensive explanation that to see loyal customers to Electric Rail Train (KRL) services, companies must focus on providing high-quality services, covering all aspects of customer interaction with the services provided. This study uses a sample of 150 student and community respondents. The structural equation model analysis method was used in this study. The research design is causal and aims to test the direct influence and moderation effect between variables. The software used is SmartPLS (Partial Least Square). The results of the study show First, Service Quality has a positive effect on Customer Loyalty, the hypothesis is accepted. Second, Facility does not have a positive effect on Customer Loyalty, the hypothesis is rejected. Third, customer satisfaction has a significant effect on customer loyalty, the hypothesis is accepted. Fourth, customer satisfaction moderates service quality to customer loyalty, the hypothesis is accepted. Fifth, customer satisfaction cannot moderate between facilities and customer loyalty, the hypothesis is rejected. The implication of the results of this research is that KRL companies must focus on improving the quality of services and facilities to increase customer satisfaction and customer loyalty. This can be done by updating and developing facilities, such as trains and stations, cleanliness and punctuality.